2018
DOI: 10.1590/2175-8239-jbn-3842
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Protein Diet on lipid and anthropometric profiles of patients with chronic kidney disease on conservative management

Abstract: LPD prescribe to non-dialysis CKD patients for six months was able to improve some cardiovascular risk factors as overweight and plasma lipid profile, suggesting that LPD can be also an important tool for protection against cardiovascular diseases in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
1
5
0
1
Order By: Relevance
“…In the present study, most of the lipid fractions evaluated were within the normal range, especially for the concentrations of TC and LDL-c that were statistically higher in females. In agreement, the results of Da Silva et al 44 , Fontes et al 45 , Rizzetto et al 46 showed similar values when evaluating the lipid profile of renal dialysis patients.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the present study, most of the lipid fractions evaluated were within the normal range, especially for the concentrations of TC and LDL-c that were statistically higher in females. In agreement, the results of Da Silva et al 44 , Fontes et al 45 , Rizzetto et al 46 showed similar values when evaluating the lipid profile of renal dialysis patients.…”
Section: Discussionsupporting
confidence: 84%
“…Regarding the influence of protein intake on the lipid profile, as shown in table 6, there was a slight negative correlation, but was significant between TC, LDL-c and protein intake. These findings indicate that patients with CKD with higher protein intake had lower values of TC and LDL-c. A study by Fontes et al 45 among CKD patients conducted an intervention consisting of changing the usual hyperprotein diet (1.4g/kg) to a hypoprotein diet (0.8 g/kg) for a period of 6 months. After this period, the authors found a significant reduction in the values of TC and LDL-c in 12% and 16%, respectively, so protein intake showed a significant positive association (p<0.05) with these variables.…”
Section: Discussionmentioning
confidence: 99%
“…A small, randomised trial of 40 stage-2 CKD patients showed an improvement in lipid parameters by the Mediterranean diet for 3 months but no GFR changes [21]. A low or very low protein diet may improve lipid parameters in CKD patients [22,23] and a low fat diet may improve lipid profile in renal transplant recipients [24]. However, according to a meta-analysis of small trials, a very low protein diet supplemented with keto-analogues has no effect on lipid parameters in ESKD patients [25].…”
Section: Diet and Lifestyle Modificationsmentioning
confidence: 99%
“…Dietary components may modify lipid levels, blood pressure, oxidative stress, inflammatory processes, insulin sensitivity, and many others [130,131]. Dyslipidemia in CKD patients may be improved with adequate diet [132]. It seems that diet might influence the risk factors for kidney injury and cardiovascular disease [129].…”
Section: Diets Helping To Lower Cholesterol Levelmentioning
confidence: 99%
“…Fontes et al [132] found that a low-protein diet prescribed for six months to patients with pre-dialysis CKD not only reduced total cholesterol and LDL-C but also helped to preserve renal function and diminished serum levels of uric acid. According to authors the lowering of serum levels of total cholesterol and LDL-C observed in this study was not surprising.…”
Section: Diets Helping To Lower Cholesterol Levelmentioning
confidence: 99%